Recombinant Factor IX Recovery and Inhibitor Safety: A Canadian Post-licensure Surveillance Study - Poon, Man-Chiu; Lillicrap, David; Hensman, Caroline; Card, Robert; Scully, Mary-Frances; Members of Asso cia tion of Hemophilia Clinic Directors of Canada* and Canadian Association of Nurses in Hemophilia Care* (Thrombosis and Haemostasis, 2002)
As part of the Canadian post-licensure surveillance on the safety of recombinant factor IX (rFIX, BeneFIX®), factor IX recovery and inhibitor development were studied. The recovery following rFIX infusion in 126 patients (mean = 0.77, median 0.72, range 0.36-1.85, 95% CI of mean 0.74-0.81, expressed as FIX activity increase in U/dL per IU FIX concentrate/kg body weight infused) was significantly lower than that following the last plasma-derived factor IX (pdFIX) infusion in 74 patients (mean 1.05, median 1.00, range 0.37-2.29, 95% CI of mean 0.99-0.97). The recovery for rFIX for patients aged ≤15 years (n = 41, mean recovery 0.64) and that for patients aged >15 years (n = 85, mean 0.84) was each significantly lower than that for pdFIX (aged ≤15 years: n = 21, mean recovery 0.91; aged >15 years: n = 53, mean recovery 1.10). For both rFIX and pdFIX concentrates, the recovery was lower in patients ≤15 years of age compared to those >15 years of age. Similar data and conclusions were obtained on 66 patients with paired recovery data from rFIX and pdFIX. Overall, our data are similar to those obtained in formal clinical trials. Two of 244 patients treated with rFIX for up to 5 years have developed de novo inhibitors associated with anaphylaxis, an incidence that is similar to that reported for pdFIX. No other serious adverse events, including thrombotic episodes, were reported. To the best of our knowledge, this is the first formal report of recovery and inhibitor formation on rFIX in a peer-reviewed manuscript form.
Keywords: Recombinant factor IX; plasma-derived factor IX; recovery; inhibitor; surveillance; safety